Mesostructured silica nanoparticles supported electrosynthesized goethite in cationic surfactant for photodegradation of 2-chlorophenol - Rohayu Jusoh, 1989- author; Aishah Abdul Jalil, supervisor; Sugeng Triwahyono; Ani Maulud, supervisor; Fakulti Kejuruteraan Kimia (2015)
Thesis (Ph.D (Kejuruteraan Kimia)) - Universiti Teknologi Malaysia, 2015